Optimalisasi Performans Sapi Bali Melalui Pemberian Pakan Konsentrat dan Inseminasi Buatan di Kabupaten Buleleng, Bali - Budiari, Ni Luh Gede; Kertawirawan, I Putu Agus; Yasa, I Made Rai; Adijaya, I Nyoman (Jurnal Veteriner; Vol 22 No 1 (2021), 2021)
Research related to the optimization of cow performans is done through concentrate feed and reproduction technology. This research was conducted in 2018 in Musi Village, Gerokgak Sub-district, Buleleng Regency, Bali. The study used a Completely Randomized Design (CRD) with 4 feed treatments and used 7 pregnant cows as replicates. The treatment is carried out when the cows enters 7 months pregnancy. Treatments tested: P0 cows given forage + rice bran 1 kg /cow/day + Bio Cas 5 ml/cow/day (mating with males), P1 = P0 cows mated with Artificial Imsemination (IB), P2 cows given forage + concentrates 1 kg/cow/day + bio cas 5 ml/cow/day (mating with a male), and P3 = P2 cattle mated with IB. Parameters observed that the parent body weight, weight gain calf, calf birth weight, weaning weight, calving interval, dry matter intake and feed rations convertions ratio. Data were analyzed by analysis of variance, if there are significant differences (P <0.05), followed by LSD 5%. The results showed that cows given feed concentrates and mated with IB (P3) result in weight gain of 0.52 kg/calf/ day was significantly higher (P <0.05) of P0 (0.40 kg/calf/day). Consumption of dry matter ration for P3 (2.59 kg) was significantly less (P <0.05) than P0 (2.87 kg) and resulted in the highest weight gain causing P3 FCR value of 4.98 was significantly lower than P0. Calf birth weight of all treatments showed no significant difference (P>0.05), but calf weight gain for P3 0.57 kg/calf/day was highest (P <0.05) compared to treatments P0 and P1 so that weaning weight calves P3 to 121.43 kg was significantly higher (P <0.05) than treatments P0 and P1. Estrus post partus for P3 is 2.87 months and calving interval is 12.36 months shorter than other treatments. This shows that the cows whose given concentrate feed mated through artificial insemination / males cattle produces the highest birth weight and calf weaning and short calving intervals.